Peak Pruritus Numerical Rating Scale: psychometric validation and responder definition for assessing itch in moderate‐to‐severe atopic dermatitis. (1st October 2019) - Yosipovitch, G.; Reaney, M.; Mastey, V.; Eckert, L.; Abbé, A.; Nelson, L.; Clark, M.; Williams, N.; Chen, Z.; Ardeleanu, M.; Akinlade, B.; Graham, N.M.H.; et al.
Summary: Background: Moderate‐to‐severe atopic dermatitis (AD) is a chronic disease characterized by intense, persistent and debilitating itch, resulting in sleep deprivation, signs of anxiety and depression, impaired quality of life and reduced productivity. The Peak Pruritus Numerical Rating Scale (NRS) was developed and validated as a single‐item, patient‐reported outcome (PRO) of itch severity. Objectives: To describe the content validity and psychometric assessment (test–retest reliability, construct validity, known‐groups validity, sensitivity to change) of the Peak Pruritus NRS, and to derive empirically a responder definition to identify adults with a meaningful change in itch. Methods: Content validity was assessed through in‐depth patient interviews. Psychometric assessments used data from phase IIb and phase III dupilumab clinical trials and included test–retest reliability, construct validity, known‐groups validity and sensitivity to change in patients with moderate‐to‐severe AD. Results: Interview participants indicated that the Peak Pruritus NRS was a relevant, clear and comprehensive assessment of itch severity. Peak Pruritus NRS scores showed large, positive correlations with existing PRO measures of itch, and weak or moderate correlations with clinician‐reported measures assessing objective signs of AD. Peak Pruritus NRS score improvements were highly correlated with improvements in other itch PROs, and moderately correlated with improvements in clinician‐reported measures assessing objective signs of AD. The most appropriate threshold for defining a clinically relevant, within‐person response was ≥ 2–4‐point change in the Peak Pruritus NRS. Conclusions: The Peak Pruritus NRS is a well‐defined, reliable, sensitive and valid scale for evaluating worst itch intensity in adults with moderate‐to‐severe AD.